Quantitative imaging of 2 nm monolayer-protected gold nanoparticle distributions in tissues using laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS). Issue 8 (16th March 2016) - Elci, S. Gokhan; Yan, Bo; Kim, Sung Tae; Saha, Krishnendu; Jiang, Ying; Klemmer, Gunnar A.; Moyano, Daniel F.; Tonga, Gulen Yesilbag; Rotello, Vincent M.; Vachet, Richard W.
Abstract : Imaging reveals that AuNPs remain intact and their surface chemistry influences how they interact with different organs. Abstract : Functionalized gold nanoparticles (AuNPs) have unique properties that make them important biomedical materials. Optimal use of these materials, though, requires an understanding of their fate in vivo . Here we describe the use of laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) to image the biodistributions of AuNPs in tissues from mice intravenously injected with AuNPs. We demonstrate for the first time that the distributions of very small (∼2 nm core) monolayer-protected AuNPs can be imaged in animal tissues at concentrations in the low parts-per-billion range. Moreover, the LA-ICP-MS images reveal that the monolayer coatings on the injected AuNPs influence their distributions, suggesting that the AuNPs remain intact in vivo and their surface chemistry influences how they interact with different organs. We also demonstrate that quantitative images of the AuNPs can be generated when the appropriate tissue homogenates are chosen for matrix matching. Overall, these results demonstrate the utility of LA-ICP-MS for tracking the fate of biomedically-relevant AuNPs in vivo, facilitating the design of improved AuNP-based therapeutics.